Análisis de Cambio de Cobertura, Fragmentación y Conectividad Ecológica entre los complejos de páramos del Departamento de Nariño, Colombia (2025)
This study analyzed changes in coverage, fragmentation, and ecological connectivity in the páramo complexes of the Nariño department in Colombia during the periods 2005-2010 and 2018-2020. Information from the Páramos Mapping of Colombia, at a scale of 1:100,000, was used, and to quantify the spatial and temporal changes in land cover and land use, the layers of the IDEAM land cover maps corresponding to the periods 2005-2009, 2010-2012, 2018, and 2020 were reclassified.